Disturbance-observer-based nonlinear control for overhead cranes subject to uncertain disturbances - Wu, Xianqing; Xu, Kexin; He, Xiongxiong (Mechanical systems and signal processing, 2020)
•A finite time nonlinear control method, along with a finite time disturbance observer, is proposed for the crane control.•The disturbance can be estimated in finite time and the closed-loop system’s states are convergent in finite time.•The proposed method is continuous without any chattering, which is convenient for practical applications. The regulation and disturbance rejection problems of the underactuated overhead crane system in the presence of uncertain disturbances are considered in this paper. A novel nonlinear control method, along with a finite time disturbance observer, is proposed for the crane system. Different from existing control methods, one important feature of the proposed method is that uncertain disturbances are attenuated and eliminated by the disturbance observer in finite time. More precisely, some transformations are performed with respect to the original dynamic model of the crane system. Then, a finite time disturbance observer is introduced, based on which a nonlinear control method is proposed. Rigorous mathematical analysis is implemented to prove the theoretical derivations. Finally, simulation and experimental tests are carried out to demonstrate the superior performance of the proposed method.